Predictor-based optimal robust guaranteed cost control for uncertain nonlinear systems with completely tracking errors constraint. Issue 13 (September 2019) - Wang, Minlin; Ren, Xuemei; Dong, Xueming; Chen, Qiang
Highlights: A state predictor is combined with the neural dynamic surface control to use the predictor error to update the neural network. A prescribed performance function is used in the state predictor to guarantee the prescribed performance of prediction error. An optimal robust guaranteed cost control is designed to handle the uncertainties and guarantee the cost function is bounded. Simulation and experimental results have been conducted to validate the effectiveness of the proposed controller. Abstract: In this paper, a novel composite controller is proposed to achieve the prescribed performance of completely tracking errors for a class of uncertain nonlinear systems. The proposed controller contains a feedforward controller and a feedback controller. The feedforward controller is constructed by incorporating the prescribed performance function (PPF) and a state predictor into the neural dynamic surface approach to guarantee the transient and steady-state responses of completely tracking errors within prescribed boundaries. Different from the traditional adaptive laws which are commonly updated by the system tracking error, the state predictor uses the prediction error to update the neural network (NN) weights such that a smooth and fast approximation for the unknown nonlinearity can be obtained without incurring high-frequency oscillations. Since the uncertainties existing in the system may influence the prescribed performance of tracking error and the estimation accuracy of NN, an optimal robust guaranteed cost control (ORGCC) is designed as the feedback controller to make the closed-loop system robustly stable and further guarantee that the system cost function is not more than a specified upper bound. The stabilities of the whole closed-loop control system is certified by the Lyapunov theory. Simulation and experimental results based on a servomechanism are conducted to demonstrate the effectiveness of the proposed method.